FRI0461 Immunosuppressive "Routine" Treatment of of SSC Patients with Interstitial Lung Disease – Results of the FP7 Desscipher Project of the Eustar Group. (9th June 2015) - Huscher, D.; Adler, S.; Siegert, E.; Allanore, Y.; Czirják, L.; Del Galdo, F.; Denton, C.P.; Distler, O.; Foeldvari, I.; Frerix, M.; Matucci-Cerinic, M.; Mueller-Ladner, U.; et al.
Abstract : Background: Interstitial lung disease (ILD) represents one of the most frequent causes of death in systemic sclerosis (SSc) patients. Yet, there are no approved drugs for treatment of SSc-ILD, consensus of management is difficult, and evidence-based data facilitating a treatment algorithm for everyday practice are lacking. Objectives: To describe immunosuppressive treatment and prescription patterns in patients with SSc-ILD. Methods: The European League against Rheumatism – Scleroderma Trial and Research (EUSTAR) database was established in 2004 to collect annually data on specialized care of patients with SSc. Based on this database, the FP7 DeSScipher project consisting of several observational trials was initiated, of which one focuses on ILD. The EUSTAR database was analyzed with respect to immunosuppressive therapy. Results: Out of a cohort of 11, 496 SSc patients, we identified 3, 778 adult patients fulfilling the ACR or according to available data the new ACR-EULAR criteria, additionally showing signs of ILD (either on plain X-ray or high resolution computed tomography) with at least one report on immunosuppressive treatment. Mean age was 55.5±13.4 years, with 83.6% females and a mean SSc disease duration of 8.5±7.9 years. Mean mRSS was 10.6±8.7, 44.4% had diffuse skin involvement, 46.9% the limited SSc subtype, and 7.5% sclerodactyly only. Compared to the 2, 681 (71%) patients who had at least one episode of immunosuppressive therapy the 1, 097 (29%) patients without use of immunosuppressants ever were on average 5 years older, had longer disease duration (3.2 years), more often limited skin involvement, higher DLCO and FVC values.The immunosuppressants most frequently used were prednisolone (pred) (58.8%), cyclophosphamide (cyc) (19.1%), azathioprine (aza) (15.0%), methotrexate (mtx) (14.7%), and mycophenolate mofetil (mmf) (13.1%), all others were prescribed in less than 3%. With regard to highest treatment intensity ever received, similar proportions of patients got monotherapies (34.0%) and combinations of two drugs (32.4%), while triple therapy was comparably rare with 4.1%. When comparing patient characteristics at treatment start of the most frequent regimens, differences compared to the "never IS" group and between treatment arms become apparent (table 1 ). Conclusions: "Everyday" use of immunosuppressants is frequent in SSc-ILD patients showing a wide variety of single and combined substances with distinct patient patterns between treatment regimens. However, prospective studies are still necessary to define indications and outcomes. The EU-funded international FP7 DeSScipher research project was initiated to achieve this goal, comprising 5 prospective observational trials addressing the most frequent medical problems in SSc patients. Acknowledgements: This study was supported by the Seventh Framework Program of European Commission as part of the DeSScipher Project (grant agreement No. 305495). Disclosure of Interest: D. Huscher: None declared, S. Adler: None declared, E. Siegert: None declared, Y. Allanore: None declared, L. Czirják: None declared, F. Del Galdo: None declared, C. P. Denton Grant/research support from: Actelion, CSL Behring, Novartis, Consultant for: Actelion, GSK, Bayer, Inventiva, Takeda, O. Distler Grant/research support from: or consultant fees: 4D Science, Actelion, Active Biotec, Bayer-Schering, Biogen, Biovitrium, BMS, Boehringer Ingelheim Pharma, EpiPharm, Ergonex, GSK, Inventiva, Medac, Novartis, Pfizer, Pharmacyclics, Roche/Genentech, Sanofi/Genzyme, Serodapharm, Sinoxa and United BioSource Corporation., I. Foeldvari: None declared, M. Frerix: None declared, M. Matucci-Cerinic: None declared, U. Mueller-Ladner: None declared, I. H. Tarner Grant/research support from: and speaker's honoraria from Abbvie, Actelion, BMS, Chugai, Pfizer, Roche and UCB, G. Valentini: None declared, U. A. Walker Consultant for: manufacturer of Ilaris, G. Riemekasten: None declared